Modelling and Monitoring of Coastal Marine Processes - Murthy, Raj C.; Sinha, P.C; Rao, Y.R (Springer Netherlands : Imprint: Springer, 2008)
Although numerous books have been written on both monitoring and modelling of coastal oceans, there is a practical need for an introductory multi-disciplinary volume to non-specialists in this field. The articles commisioned for this book, organized into four major themes, are written by experts in their disciplines while the text is intended for scientists who do not have extensive training in marine sciences and coastal zone management. As such, the articles in this monograph can be a valuable reference for practicing professionals. The first section introduces the complex physical processes with main emphasis on waste disposal in the coastal ocean. Following this, examples of instrumentation techniques that are commonly used for measuring different properties of oceans are discribed. Coastal and estuarine transport and dispersion modelling is introduced in the next section with examples from different parts of the world. The last section provides an overview of coastal disasters such as tropical cyclones, storm surges and oil spills.